Beautiful Soon Enough - Berdeshevsky, Margo (Book collections on Project MUSE., 2011)
Winner of FC2's American Book Review/Ronald Sukenick Innovative Fiction Prize Margo Berdeshevsky & rsquo;s Beautiful Soon Enough is a collection of hypnotic stories that capture the lives & mdash;worldly, sexual, obsessive & mdash;of twenty & ndash;three arresting women. These are snapshots and collages: stories of women on the outside, looking in; of women content to end their affairs; of young women learning the power of seduction; and of older women reminiscing about past loves. They are women who cannot live without love & rsquo;s embrace, and women who have found it and feel that it is never enough.